Keeping milk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The collection of milk is not well developed in West Africa. According to the World Bank, more than 5 million litres are lost annually because milk cannot be kept during transport. One solution for farmers in isolated areas is the LPS system, which...